Assessment Of Genetic Diversity Among Kidney Bean (Phaseolus Vulgaris L.) Cultivars Using Est-Simple Sequence Repeat (Ssr) Markers (Applied Biological Research, 2018)
Genetic variation among kidney bean (Phaseolus vulgaris L.) cultivars, procured from the farmers of Kinnaur district of Himachal Pradesh (India), was evaluated using EST-SSR markers. A total of 25 primers were used out of  which 19 primers showed amplification. The total n0umber of bands amplified  was 26, out of which 24 were polymorphic and 2 were monomorphic. On an  average, the number of bands generated primer-1 was 1.37 of which 1.26 was  polymorphic and 0.11 were monomorphic. Seven primers produced 14 bands  (2 bands primer-1) and only one band each was obtained with remaining  primers. The number of unique bands were 2 and the size of amplified product  from 70 to 800 bp. Similarity between cultivars estimated as per  Jaccard’s coefficients ranged from 0.17-0.90 indicating substantial diversity in  bean cultivars. Maximum similarity coefficient (0.90) was between ‘Capsule’ and ‘Kaju’ cultivars while minimum (0.17) between ‘Chitra’ and ‘Luxmi’.  Dendrogram grouped cultivars into two major clusters. The PIC value was  highest for primer SP5.
Keywords: Genetic diversity; Phaseolus vulgaris; polymorphism; simple sequence repeat marker